The debtor-attributes information and the probability of performing loans in the microfinance sector - Bayu Sindhu Raharja (Jurnal Manajemen dan Pemasaran Jasa, 2021)
Based on the recent evidence of the high rate of non-performing loans in Indonesia’s microfinance sector, there is a need to formulate a mechanism that could control such credit risk. This study attempts to identify the pivotal determinant factorsresponsible for performing loans. In particular, this research proposes demand-side factors, such as debtor-attributes information, as critical for ensuring installment payments. Using unique data from microfinance in Central Java, it employs logistic regression analysis to prove that debtors’ age and type of collateral significantly affect loan performance. This paper further shows that other variables, such as the payment period and the interest rate, also substantially affect credit risk. These findings have empirical and practical significance. For practical purposes, this research develops the new perspective that debtor-specific information, particularly on their behavioral aspects, requires more in-depth review. This insight may be useful for developing new credit-analyzing tools to alleviate severe non-performing loans. Empirically, this research improves the study of antecedent variables that influence performing loans.